Integrating Augmented Reality (AR) in higher education: A breakthrough in EFL reading instruction - Mustakim Sagita; Issy Yuliasri; Abdurrahman Faridi; Hendi Pratama (English Learning Innovation, 2025)
Despite growing interest in Augmented Reality (AR) in language education, few studies have systematically evaluated its impact on EFL reading comprehension or examined instructors’ perspectives, particularly in Indonesian contexts. This study employed a quasi-experimental mixed-methods design to investigate the effectiveness of Assemblr EDU, an AR-based application, in enhancing reading comprehension among 104 B1-level Indonesian EFL undergraduates. Using the Dialang test and one-way ANCOVA, results showed a significant improvement in the experimental group’s posttest scores (M = 15.61) compared to the control group (M = 12.43), with a large effect size (partial η² = .919, p < .001). The mean difference of -2.808 (p = .000) confirms the substantial advantage of AR integration. Qualitative data from semi-structured interviews with six experienced lecturers, thematically analyzed, revealed that AR fostered student motivation, vocabulary retention, and conceptual understanding through multimodal interaction. However, technical limitations and access issues were identified as persistent challenges. The findings support AR’s pedagogical relevance in EFL reading instruction, though successful implementation demands infrastructural readiness and teacher training.